The Correlation of Higher Order Thinking Skills and Work Readiness of Vocational High School Students - Hasan, Arsyadani; Pardjono, Pardjono (Jurnal Pendidikan Teknologi dan Kejuruan, 2019)
Higher Order Thinking Skills (HOTS) are required to face a fast-changing and unpredictable situation or condition in the future. This study describes the HOTS profile of Vocational High School (VHS) students in Surakarta and its correlation with the work readiness in the field of mechanical engineering. The students’ HOTS data were collected through the lathe technique examination, which has been tested empirically and validated by the subject matter. The result of the study showed that the HOTS profile of VHS students of mechanical engineering categorized as high, moderate and low were 36.81%, 18.68%, and 44.5% respectively. The higher thinking level of VHS students showed that students' work readiness was also higher. This means that HOTS was related to psychological, physical, and experiential aspects of the students. The result of HOTS profile could be used by the VHS teachers as the  basis to provide high quality lessons to produce graduates equipped with HOTS and better competitiveness and professionalism in workplaces.